Perceptions of COVID-19 Mask Use in Mozambique: A Call for Effective Community Education - Alexandre, Germito de Castro; Tipanoa, Ninla Carlos (GNOSI: An Interdisciplinary Journal of Human Theory and Praxis, 2022)
Masks have been essential since COVID-19's emergence. Face masks are often stigmatised and misunderstood by Mozambique's natives. To fight the myths and stigma in Mozambique's communities, comprehensive community education is needed. This research explored the natives' views of face masks' usage to prevent COVID-19 in Mozambique. Descriptive quantitative research was used to carry out this research. A total of 361 Mozambique islanders were sampled. This research also adopted random probability sampling. Data collection was done through the use of a questionnaire. To ensure validity, the study instruments were reviewed by the Center for Cultural and Religious Studies of the Indian Ocean and other specialists from Universidade Lúrio's Faculty of Social and Human Sciences. This research reveals that people on the island of Mozambique used face masks because they feared police arrest; there was no effective community education to convince them to do so. The research suggests some recommendations that will help improve the use of masks to prevent the spread of COVID-19 infection as well as future unforeseen pandemics.